PENGARUH IKLIM ORGANISASI DAN EFIKASI DIRI TERHADAP KEPUASAN KERJA DAN DAMPAKNYA TERHADAP KINERJA KARYAWAN BANK ACEH SYARIAH KANTOR CABANG BIREUEN - Roni, Jeffri; Evi; Muhammad (IndOmera, 2024)
This research aims to analyze (1) the influence of organizational climate and the influence of self-efficacy on employee job satisfaction. (2) analyze the influence of organizational climate through job satisfaction on employee performance. (3) the influence of self-efficacy through job satisfaction on employee performance. The object of the research is employees of Bank Aceh Syariah (BAS) Bireuen Branch. Through associative research with a path analysis approach. The research results show: Organizational climate has a significant effect on job satisfaction of employees of Bank Aceh Syariah Bireuen Branch Office with a percentage of 15%. This means that organizational climate has a contribution of 15% in increasing employee job satisfaction, while self-efficacy has a contribution of 6.8% in increasing employee job satisfaction. Organizational climate has a significant influence on the performance of employees of Bank Aceh Syariah Bireuen Branch Office and contributes 44.7% in improving employee performance, while self-efficacy has a contribution of 24.9%. Job satisfaction has a significant effect on the performance of Bank Aceh Syariah employees at the Bireuen Branch Office and has a direct influence of 21.7%. Job satisfaction can mediate the influence of organizational climate on employee performance and self-efficacy on employee performance at Bank Aceh Syariah Bireuen Branch Office.